The policing of burglary at a residential premises in the Ga-Molepo Village, Limpopo Province - Malatjie, Beauty Mogaladi (My University, 2023)
The primary aim of this study was to explore policing of burglary at a residential prem-ises within the Ga-Molepo community. From a qualitative standpoint, data was gath-ered through semi-structured In-depth Individual Interviews (IDIIs). The participants were selected from Tshebela, Rampheri, Mogano and Tshebela. Moreover, a compre-hensive review of the relevant literature and the Broken Window Theory (BWT) was conducted and reviewed to obtain a better understanding of this study. A thematic content analysis procedure was followed to analyse the gathered data. This study was guided by the following objectives:  The prevalence of burglary at a residential premises in the Ga-Molepo community.  To identify the problems experienced by the Ga-Molepo community with policing of burglary.  The effectiveness of policing of burglary in the Ga-Molepo community. The researcher identified that more training is required and more forensic investigators are needed in the South African Police Service (SAPS), because the police are not capable of preventing residential burglary but only respond to crimes that have already been committed (Reactive-policing) and only deal with the burglary backlogs of cases that are already in the SAPS system. The study implemented the Broken Window Theory as a guide for exploring the policing of burglary at a residential premises. The employed theory (Broken Widows Theory - BWT), in reference to societal order, pro-poses that societies must be cautious against the least criminalities. If such disorders or small crimes are not taken seriously, more serious crime can be committed as a result. The police must take all crime as seriously, irrespective of its nature. If the police uphold their old-style role as night guards in opposition of threats to order, then the society flourishes. To advance policing in South Africa through BWT or other ap-proaches we need to raise a culture and capability of planning and evaluating police practices
Thesis (M. A. (Criminology)) -- University of Limpopo, 2023
Keywords: Burglary at a residential premises; Ga-Molepo village; Limpopo Province; Policing; Burglary -- South Africa -- Limpopo Province; Community policing -- South Africa -- Limpopo